2021
DOI: 10.1038/s41598-021-83096-1
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Cardiology/European Society of Hypertension versus the American College of Cardiology/American Heart Association guidelines on the cut-off values for early hypertension: a microvascular perspective

Abstract: The aim of this study was to investigate retinal and peripheral microvascular function in asymptomatic individuals that fall into different BP groups when using either the ESC/ESH or the ACC/AHA guidelines. Retinal and peripheral microvascular function was assessed in 358 participants by means of dynamic retinal vessel analysis and digital thermal monitoring, respectively. Blood pressure and lipid panel were also evaluated. Retinal vascular function measured in all groups belonging to the ACC/ASH classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Standard anthropometric measures of height and weight were recorded to determine body mass index (BMI = weight/height). Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured using an automatic blood pressure monitor (UA-767; A&D Instruments Ltd., Abingdon, UK) to determine mean arterial pressure (MAP = 2/3 DBP + 1/3 SBP) [24]. Intra-ocular pressure (IOP) readings were obtained using non-contact tonometry (Pulsair; Keeler Ltd., Winsor, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Standard anthropometric measures of height and weight were recorded to determine body mass index (BMI = weight/height). Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured using an automatic blood pressure monitor (UA-767; A&D Instruments Ltd., Abingdon, UK) to determine mean arterial pressure (MAP = 2/3 DBP + 1/3 SBP) [24]. Intra-ocular pressure (IOP) readings were obtained using non-contact tonometry (Pulsair; Keeler Ltd., Winsor, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Standard anthropometric measures of height and weight were recorded to determine body mass index (BMI = weight/height 2 ). Systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were measured using an automatic Blood Pressure monitor (UA-767; A&D Instruments Ltd., Abingdon UK) [ 13 ] to determine mean arterial pressure (MAP = 2/3 DBP + 1/3 SBP) [ 14 ]. Intraocular pressure (IOP) readings were obtained using non-contact tonometry (Pulsair; Keeler Ltd., Winsor, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Retinal vessel reactivity was assessed using the dynamic retinal vessel analyzer (DVA, IMEDOS GmbH, Jena, Germany) in accordance with an already established protocol ( Figure 1 ) [ 4 , 31 ]. Only one randomly selected eye was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, many methods were developed to evaluate functional microvascular responses to biological stimuli in different vascular beds [ 2 ]. One of these methods, the dynamic retinal vessel analysis (DVA), was highlighted as one of the most sensitive and reliable methods to measure early vascular changes that point out early endothelial dysfunction and future risk of cardiovascular pathologies in individuals with and without overt clinical symptoms [ 3 , 4 , 5 ]. Moreover, it has also been shown that retinal microvascular function is modified by age [ 6 ].…”
Section: Introductionmentioning
confidence: 99%